2002
DOI: 10.1051/forest:2002014
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing base-cation immobilization in the stem of six hardwoods of eastern Canada

Abstract: -Rates of base-cation immobilization in the stem of basswood, beech, red oak, red maple, sugar maple and white ash were compared to identify the relative potential for impoverishing soils. Two natural stands in southern Quebec were studied. Allometric equations predicting stem nutrient content from stem diameter were developed. Between 20 and 25 trees per species were sampled for age and stem diameter at breast height, and the area covered by the projection of the tree crown on the ground. Rates of K, Ca and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Numerous studies have documented the control of individual tree species on soil properties both within plantations (Challinor 1968;Alban 1982) and by individual trees in mixed stands (Boettcher and Kalisz 1990;Finzi et al 1998a, b;Boucher and Coˆte´2002;Dijkstra and Smits 2002;Dijkstra 2003). We likewise found significant species-related differences in transfer of base cations in canopy exchange and litterfall and transformation of base cations from mineralization + weathering (Table 3; Figures 1-3).…”
Section: Individual Tree Species and The Pattern Of Northern Hardwoodmentioning
confidence: 98%
“…Numerous studies have documented the control of individual tree species on soil properties both within plantations (Challinor 1968;Alban 1982) and by individual trees in mixed stands (Boettcher and Kalisz 1990;Finzi et al 1998a, b;Boucher and Coˆte´2002;Dijkstra and Smits 2002;Dijkstra 2003). We likewise found significant species-related differences in transfer of base cations in canopy exchange and litterfall and transformation of base cations from mineralization + weathering (Table 3; Figures 1-3).…”
Section: Individual Tree Species and The Pattern Of Northern Hardwoodmentioning
confidence: 98%
“…Nutrient concentrations may vary within tree stems in both the vertical and horizontal directions in different ways, depending on element and tree species [13,15,37,41]. Bark usually has higher nutrient concentrations than the rest of the stem [13,40,44,52], while differences between heartwood and sapwood seem to be more variable depending on species and nutrient elements [31].…”
Section: Nutrients In the Stem Woodmentioning
confidence: 99%
“…The study of Canadian hardwoods referred to above [13] showed that while the Ca concentration in the heartwood of red oak was low; the concentration in bark was about twice that in beech. If the same is true for European species, this may partly explain why the Ca concentrations in oak and beech were similar in our study, as the bark was included in the analysed samples.…”
Section: Nutrients In the Stem Woodmentioning
confidence: 99%
See 2 more Smart Citations